2021
DOI: 10.3390/ijms221810171
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ce3+ Substitution on Antimicrobial and Antibiofilm Properties of ZnCexFe2−xO4 Nanoparticles (X = 0.0, 0.02, 0.04, 0.06, and 0.08) Conjugated with Ebselen and Its Role Subsidised with γ-Radiation in Mitigating Human TNBC and Colorectal Adenocarcinoma Proliferation In Vitro

Abstract: Cancers are a major challenge to health worldwide. Spinel ferrites have attracted attention due to their broad theranostic applications. This study aimed at investigating the antimicrobial, antibiofilm, and anticancer activities of ebselen (Eb) and cerium-nanoparticles (Ce-NPs) in the form of ZnCexFe2−XO4 on human breast and colon cancer cell lines. Bioassays of the cytotoxic concentrations of Eb and ZnCexFe2−XO4, oxidative stress and inflammatory milieu, autophagy, apoptosis, related signalling effectors, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 153 publications
1
5
0
Order By: Relevance
“…This action is attributed to the interaction of the NPs with the exopolysaccharides and the proteins exerted by the biofilms for attachment, thus preventing the formation of the biofilm [52,60]. In accordance with the use of the same concentrations of the nano-ferrites on the bacterial biofilms in the current study, morphological changes in the bacterial cells were observed, followed by complete lysis of the cells, thus destroying the pre-formed biofilms [61]. were dissolved in deionized water and stirred for 30 min.…”
Section: The Antibacterial Activity Of the Mg033ni033co033laxfe2−xo4 Npssupporting
confidence: 83%
“…This action is attributed to the interaction of the NPs with the exopolysaccharides and the proteins exerted by the biofilms for attachment, thus preventing the formation of the biofilm [52,60]. In accordance with the use of the same concentrations of the nano-ferrites on the bacterial biofilms in the current study, morphological changes in the bacterial cells were observed, followed by complete lysis of the cells, thus destroying the pre-formed biofilms [61]. were dissolved in deionized water and stirred for 30 min.…”
Section: The Antibacterial Activity Of the Mg033ni033co033laxfe2−xo4 Npssupporting
confidence: 83%
“…S1M). The polydispersity index (PDI) calculated from DLS data, where PDI values < 0.05 are fit best to the monodisperse model, whereas PDI values > 0.7 are considered to indicate a polydispersity diffusion of particles [ 32 ]. In our study, the synthesized Nano-Se has a PDI value of 0.085, indicative of a medium dispersity.…”
Section: Resultsmentioning
confidence: 99%
“…As reported, UV activation of the prepared CdS nanocomposite may produce more OH free radicals. The electron mediator diffuses inside microbial cells and the tested CdS nanocomposite generates free OH radicals which in return destroys microbial cells through microbial coenzymes destruction and reduction of their contents [ 69 ]. As reported, many metal oxide NPs possess net positive charge on their surface while negative charge was found in the outer layer of the tested microbial cells which simply enables the electrostatic attraction leading to the oxidization of cell components and subsequent microbial cell lysis [ 70 ].…”
Section: Resultsmentioning
confidence: 99%